Hubungan Antara Kematangan Emosi dengan Penyesuaian Diri pada Mahasiswa Perantau Universitas Negeri Padang - Vina Kurnia Azzahra (Pusat riset dan Inovasi Nasional, 2025)
This research aims to examine the relationship between emotional maturity and adjustment in migrant students at Universitas Negeri Padang. The subjects in this research were migrant students at Universitas Negeri Padang. The number of subjects taken in this research was 109 students. The method used in this research is nonprobability sampling, namely purposive sampling. The measuring instruments used in this research are the emotional maturity scale and the self-adjustment scale. The data obtained in this research were analyzed using the Pearson correlation technique. The results of this study show that there is no significant relationship between emotional maturity and self-adjustment, as shown by the value of r = 0.117 with p = 0.227 (p> 0.05). This shows that there is no relationship between emotional maturity and self-adjustment in Padang State University Migrant Students.